2018
DOI: 10.1155/2018/9490435
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Antioxidant Capacities, Organic Acids, and Volatiles of Papaya Juices Fermented by Lactobacillus acidophilus and Lactobacillus plantarum

Abstract: Fermentation of foods by lactic acid bacteria is a useful way to improve the nutritional value of foods. In this study, the health-promoting effects of fermented papaya juices by two species, Lactobacillus acidophilus and Lactobacillus plantarum, were determined. Changes in pH, reducing sugar, organic acids, and volatile compounds were determined, and the vitamin C, total phenolic content, and flavonoid and antioxidant capacities during the fermentation process were investigated. Juices fermented by Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 77 publications
10
60
0
Order By: Relevance
“…These results may be due to the short fermentation time (48 hr). Chen, Chen, Chen, Zhang, and Chen () also found that the increase of antioxidant capacities of the fermented papaya juices (48 hr) is small. These results are consistent with the present results.…”
Section: Resultsmentioning
confidence: 94%
“…These results may be due to the short fermentation time (48 hr). Chen, Chen, Chen, Zhang, and Chen () also found that the increase of antioxidant capacities of the fermented papaya juices (48 hr) is small. These results are consistent with the present results.…”
Section: Resultsmentioning
confidence: 94%
“…[34] Thirdly, acetate esters are formed by alcohol acetyltransferases from the reaction between acetyl-CoA and alcohols, as well as the availability of alcohol precursors. [35] The results demonstrated that lactic acid fermentation through selected strains increased the flavor profile of pomegranate juice. [22] Tables 7 and 8, indicates that a total of 41 volatile compounds were detected in untreated FPJ, and were grouped according to the following chemical class (Table 7): aldehydes and ketones (6 compounds identified), alcohols (10), esters (10), heterocyclic and aromatic compounds (4), acids (4), hydrocarbons (2) and miscellaneous (5).…”
Section: Treatmentmentioning
confidence: 94%
“…A decline in the total carotenoid and ÎČcarotene concentration in the probioticated beverage could be due to their oxidation at incubation temperatures. Chen et al (2018) also reported a decline in the carotenoid and vitamin C content in the probioticated papaya juice. No significant difference in the antioxidant concentration was observed between the control and the probioticated sample as is evident from the FRAP and DPPH values (Table 4).…”
Section: Antioxidant Properties Of the Probioticated Mango Beveragementioning
confidence: 91%